1992
DOI: 10.1007/bf02784616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diabetes type and treatment on zinc status in diabetes mellitus

Abstract: Zinc status was assessed in 53 diabetic patients: 18 insulin-dependent diabetic patients (IDDM), 22 noninsulin-dependent diabetic patients (NIDDM) treated with oral antidiabetic agents, and 13 insulin-treated, noninsulin-dependent diabetic patients (IRDM). Plasma zinc concentrations were in the usual range for healthy subjects in these three groups (15.3 +/- 0.9 mumol/L). Urinary zinc excretions were elevated in the IDDM group (18.3 +/- 4.1 mumol/24 h; p less than 0.01 vs normal) and in the NIDDM group (17.5 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…El Yazigi et al evaluated both Type I and II diabetics and found the absolute and creatinine corrected excretions were greater in diabetics than in matched controls and found a positive correlation between Zn excretion and hemoglobin Alc concentrations [11]. At least one study suggests that insulin treatment of diabetes may reduce the hyperzincuria while oral agents had no effect on the increased zinc excretion seen in Type II diabetes [12]. These data suggest hyperglycemia as the basis for the hyperzincuria, but since Type I and Type II patients were taking insulin or oral hypoglycemic agents which increase insulin secretion, an effect of insulin itself has not been eliminated.…”
Section: Effects Of Diabetes On Zinc Metabolismmentioning
confidence: 96%
“…El Yazigi et al evaluated both Type I and II diabetics and found the absolute and creatinine corrected excretions were greater in diabetics than in matched controls and found a positive correlation between Zn excretion and hemoglobin Alc concentrations [11]. At least one study suggests that insulin treatment of diabetes may reduce the hyperzincuria while oral agents had no effect on the increased zinc excretion seen in Type II diabetes [12]. These data suggest hyperglycemia as the basis for the hyperzincuria, but since Type I and Type II patients were taking insulin or oral hypoglycemic agents which increase insulin secretion, an effect of insulin itself has not been eliminated.…”
Section: Effects Of Diabetes On Zinc Metabolismmentioning
confidence: 96%
“…Additionally, they demonstrated a positive correlation between Zn excretion and hemoglobin A1c concentrations [23]. Honorat et al [24] found that insulin treatment of diabetes may reduce the hyperzincuria, whereas oral agents had no effects on the hyperzincuria in type II. This last study does not exclude an effect of insulin.…”
Section: Zincmentioning
confidence: 99%
“…Zinc is required for insulin production in the pancreas [16] and for insulin responsiveness in peripheral tissue [17–19]. Plasma and tissue zinc concentrations in humans and animal models with type II diabetes are lower than in normal subjects [20–23].…”
Section: Introductionmentioning
confidence: 99%